A carbon emission costing method based on carbon value flow analysis. (10th April 2020) - Zhang, Caiping; Guo, Suyuan; Tan, Lin; Randhir, Timothy O.
Abstract: Faced with increasingly strict carbon surveillance from carbon-related laws and regulations, it has become urgent for high-emission enterprises to find effective methods by which to reduce carbon emissions and control carbon emission costs. However, although carbon emission costs are closely related to the production process, current costing methods only pay more attention to the total cost amount rather than to the cost generation process. Therefore, this study aims to develop a carbon emission costing method based on carbon value flows analysis (CVFA) by tracing carbon element flow and accounting for carbon emission monetary value simultaneously. To verify the rationality and effectiveness of this method, this article also implements it in a case company. The results indicate that carbon emissions were reduced by 405, 021.97 tons, and RMB 107, 300, 000 (15, 670, 000) was saved through conducting optimized analysis. It is proved that the CVFA method is particularly suitable for process manufacturing enterprises. However, certain conditions are required to apply CVFA, such as the availability of compulsory carbon information disclosure regulations. Also, improving managers' carbon resources investment decision-making capacity can reduce more carbon emissions and save more carbon emission costs.